Claimed benefits of RTAs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
1. economies of scale, from the enlarged market over time. The goal of regional cooperation is to lower all trade barriers in order that each economy can fully pursue its comparative advantage. This will stimulate trade and draw in investment.2. the...